ANTIBACTERIAL POTENTIAL OF METHANOLIC EXTRACT OF GYROCARPUS ASIATICUS WILLD - kanta Kanthal, Lakshmi; Dey, Akalanka; Satyavathi, K.; Bhojaraju, P. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study was designed to evaluate the antibacterial activity of the methanolic extract of Gyrocarpus asiaticus Willd. Methods: The Gyrocarpus asiaticus Willd extract under study has been screened for the antibacterial activity against with Staphylococcus aureus, Escherichia coli, Salmonella typhi, Salmonella paratyphi, pseudomonas mirebelis, Pseudomonas auroginosa and Klebsiella pneumoni human pathogenic bacteria by disc diffusion method. Results: Methanolic extract showed satisfactory results against almost all the organisms, among them against E.coli it showed highest zone of inhibition 18.5mm (0.4g/ml) with the minimum inhibitatory concentration (MIC) value of 0.039 mg/ml and minimum bactericidal concentration (MBC) of 0.16mg/ml. Other Gram negative pathogens like P. mirabelis, P. auroginosa shows good zone of inhibition 13.9 mm and 17 mm (0.4g/ml) with less minimum inhibitatory concentration of 0.039 mg/ml and MBC values of 0.16 mg/ml for the above mention bacteria. But klebsiella sp was found to be resistant with no MIC, no MBC value and with a very less zone of inhibition of 7.5mm (0.4g/ml) when compared with the standards. Conclusion: From the results, it is evident that Gyrocarpus asiaticus Willd is recommended as a plant of an antibacterial agent. Keywords: Gyrocarpus asiaticus Willd, methanolic extract, antibacterial activity, MIC, MBC.